IDEALISME HUKUM SEBAGAI CONTROL SOSIAL DALAM HARAPAN MENEKAN SEKS BEBAS DIKALANGAN REMAJA - Iqbal , Muhamad; Indriani, Iin (Rechtsregel : Jurnal Ilmu Hukum, 2024)
ABSTRACT: Teenagers, especially female teens, also struggle with understanding adolescent reproductive health, according to the 2018 Indonesian Demographic and Health Survey (SDKI). K.R. For example, only 33% of female teenagers have a firm grasp of the reproductive period, 81% have dated, and roughly 44% have dated between the ages of 15 and 17. In addition, 15% of abortion cases in 2018 were related to unplanned pregnancies, and 30% of teenage girls have engaged in premarital Seks. In order to reduce premarital Seks among adolescents, it is necessary to address the following questions: How does the form of legal intervention as social control fit into the context of adolescent life? How does the idea of legal social control work? This study was qualitative, non-interactive, and used document analysis to provide interpretations of ideas, policies, and events both directly and indirectly. Whether they are inclined to engage in deviant behavior or not is determined by four basic types of connections that society has made. The four types of bonds that were previously covered are belief, participation, commitment, and attachment. Commitment recognizes "the importance of social relationships that people value, which they do not want to risk jeopardizing by engaging in criminal or deviant acts."The emotional bond that teenagers have with their family is comparable to this type of bond. Children may behave badly if their home environment is perfect, such as when parents divorce or there are family disputes. Adolescent Life: Legal Intervention as Social Control Using Micro and Macro Strategies in the Context of Adolescent Life The concept of basic bonds and the factors that influence them can be used to define the role that the law plays in social control in this regard. This is one of two possible combinations of the idea that the law serves as social control in the hope of reducing premarital Seks among adolescents.